A Comparative Study Of Traditional And Digital Accounting Systems In Managing SME Finances - Rumia Simanullang; Francisca Olivine Wardiyanti; Abdul Awim (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Effective financial management is a critical determinant of SME performance and survival. Sound financial management enables business owners to monitor cash flows, allocate resources efficiently, comply with taxation and regulatory requirements, and make informed strategic decisions. This study employs a qualitative research approach using a literature review method to examine and compare traditional and digital accounting systems in managing SME finances. A literature review is an appropriate methodological approach when the objective of the study is to synthesize, analyze, and critically evaluate existing knowledge to identify patterns, gaps, and theoretical insights within a specific research domain. This study aimed to examine and compare traditional and digital accounting systems in managing SME finances through a comprehensive literature review. Based on the synthesis of existing academic studies and institutional reports, the findings demonstrate that accounting system choice plays a crucial role in determining the effectiveness of financial management practices in SMEs.